Analisis Hukum Terhadap Restrukturisasi Badan Usaha Milik Negara (BUMN) Sektor Minyak Dan Bumi - Putri Ayu Pratiwi; Ningrum Natasya Sirait; Mahmul Siregar; Jelly Leviza (Universitas Sumatera Utara, 2019)
Abstract. The state established a SOE to seek natural wealth for the people's welfare. There are two Sector SOE of Oil and Gas namely PT Pertamina and PT PGN. In an effort to boost the performance of SOE, the Government has restructured the synergy of similar BUMN. The Government established Oil and Gas SOE Holding through Government regulation number 6 of 2018 concerning Addition of capital participation into PT Pertamina share capital. Through the Government Regulation, making Pertamina as the parent company of SOE oil and gas, PGN as a subsidiary and resulting in the status of the PT PGN Tbk Company (Persero) changing into a limited liability company that fully complies with the limited company Law, PGN is no longer a BUMN. Government regulation number 6 of 2018 as the legal basis for the establishment of the Oil and Gas Holding raises a mismatch of the legal rules between the Company Law and the BUMN Law and the State Finance Law, the State Treasury Law and the Oil and Gas Law which results in legal uncertainty. The absence of legislation governing state-owned holding increasingly makes it unclear in managing BUMN. The transfer of State shares to PGN to Pertamina resulted in PGN being subject to the Company Law. However, in the explanation of Government Regulation Number 72 of 2016, that a subsidiary in this case PGN is equated with a BUMN. Therefore, the provisions of Government Regulation Number 72 of 2016 and Government Regulation Number 6 of 2018 are only to legalize the establishment of Oil and Gas SOE Holding but do not make it absolutely a Limited Liability Company. Keywords: restructuritation, state own company, oil and gas